Risks and Dangers of the Internet: to the Problem of Informational Security for Children - Danyl’chuk, Larysa (Pedagogical Discourse, 2012)
The article deals with the general characteristics of the Internet. Key risks and dangers that exist in the network are identified. Advices and rules for Internet security and Internet ethics for children are marked out.